Sistem Informasi Inventori Gudang untuk Mengontrol Persediaan Barang pada Gudang Studi Kasus: PT. LG Indonesia - Doni, Muhamad; Fatchan, Muhamad; Hadikristanto, Wahyu (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
A system is defined as a combination of various components that are interrelated and work together, forming a unity with the aim of achieving certain targets of the system. The use of Model-Driven Web Engineering was chosen because this method is an effective basis for system development. Model-Driven Web Engineering provides developers and users with a clear view of how the system works and the developments that will be carried out. A stock system can be designed and implemented in the administration of PT LG Indonesia. Data storage in the system has been integrated with a database, enabling the inventory system to help PT LG Indonesia to reduce the potential for data loss and damage. Apart from that, fast and accurate access to data reports is also one of the advantages of this system.
Keywords: Stock of Goods; System; Model-Driven Web Engineering; Inventory